PENGGUNAAN STIMULANSIA DALAM PENYADAPAN PINUS KELAS UMUR V DAN VI DI PANINGGARAN, PEKALONGAN TIMUR (Jurnal ForestrIndo, 2024)
The Forest Management Unit (BKPH) Paninggaran, East Pekalongan falls under the pine enterprise-class, where pine resin is the main commodity. Consequently, the productivity of pine resin is highly regarded. The process of resin extraction during tapping is generally aided by stimulants. In practice, BKPH Paninggaran uses both organic and inorganic stimulants. Despite using different stimulants, BKPH Paninggaran has yet to determine which stimulant is the most effective and efficient. This study analyzes the productivity and added value of pine resin tapping when applied stimulants. The research method used a completely randomized design with a two-factor factorial. The first factor is the use of five types of stimulants. The second factor is age class V and VI. The stimulant that resulted in the highest resin productivity was the stimulant with active ingredients of ethylene and citric acid plus 5% sulfuric acid, with an average productivity of 12.98 g/quarre/day, representing a 76.44% increase in resin yield compared to the control (7.36 g/quarre/day). The productivity of pine resin in age classes V and VI did not differ significantly, being 10.13 g/quarre/day and 9.97 g/quarre/day, respectively. There was no interaction between the stimulant factor and the age class. The highest added value of the stimulant was found in the stimulant with active ingredients of ethylene and citric acid plus 5% sulfuric acid, amounting to Rp 52.76/quarre/day.